173k views
2 votes
Need help fast thanks!

Need help fast thanks!-example-1
User Axlan
by
5.4k points

2 Answers

4 votes

Hello!

Let's plug our x-value into the first equation and solve for y.

-4(2y)+11y=15

-8y+11y=15

3y=15

y=5

Now, we can plug our y-value into the second equation.

x=2(5)

x=10

Therefore, our solution is below.


\left \{ {{x=10} \atop {y=5}} \right.

I hope this helps!

User RaduM
by
5.0k points
4 votes

-4x + 11y = 15
-4(2y) + 11y = 15
-8y + 11y = 15
3y = 15
y = 15/3
y = 5
x = 2y
x = 2×5
x = 10

User Blue Orange
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.